A Study of Verb Inflection Usage in Sentences by EFL Students: Challenges and Trends - S. Madanun, Nur Rahmi; Bochari, Siska; Mochtar Marhum; Hastini (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study investigates the distribution and challenges of verb inflection usage among English as a Foreign Language (EFL) students at Tadulako University, focusing on regular verb inflection namely the use of suffixes such as -ed, -s, -ing, and -en suffixes as well as irregular verbs such as ablaut, suppletion, and zero modification in tenses and aspects. Using a quantitative descriptive approach, data were collected through tests and questionnaires from 148 third-semester students. The analysis results show that regular verbs, especially the suffix -en, are more challenging for EFL students. Seven factors that influence the use of verb inflection were identified: 1) vocabulary limitations; 2) fear of making mistakes; 3) low motivation; 4) teaching methods and quality of instruction; 5) lack of practice; 6) classroom environment; and 7) peer influence.